Social Media Interventions Strengthened COVID-19 Immunization Campaign - Di Mauro, Antonio; Di Mauro, Federica; De Nitto, Sara; Rizzo, Letizia; Greco, Chiara; Stefanizzi, Pasquale; Tafuri, Silvio; Baldassarre, Maria Elisabetta; Laforgia, Nicola (Frontiers in Pediatrics, 2022)
Background Since The Italian Medicines Agency (AIFA) has recommended the COVID-19 vaccine Comirnaty in children aged 5–11, the immunization campaign faced vaccine hesitancy in parents. Social media are emerging as leading information source that could play a significant role to counteract vaccine hesitancy, influencing parents' opinions and perceptions. Our aim was to evaluate the coverage of the COVID-19 vaccine Comirnaty in a cohort of children aged 5–11 whose families have been counseled to use Social Media to counteract vaccine hesitancy. Methods All parents of children aged 5–11 in a primary care setting were instructed by their pediatrician to get accurate information about the COVID-19 vaccine from a Facebook page. Active calls to vaccinate children were also scheduled through messaging services Pediatotem and Whatsapp. Vaccination rates of children in the study were assessed with an electronic database and compared to both regional and national child vaccination rates. Results Coverage of 277 children aged 5–11 was analyzed from 16 December 2021 to 31 January 2022. A total of 62.4% (173/277) of enrolled children received the 1st dose of COVID-19 vaccine Comirnaty and 39.7% (110/277) the 2nd dose. Coverage rates were higher compared both to the regional population (1st dose: 48.8%, 2nd dose: 24.6%; p = 0.001) and national population (1st dose: 32.1%, 2nd dose: 13.8%; p < 0.001). Conclusion Increasing vaccine confidence using Social Media interventions have a positive impact on vaccination acceptance of parents.